Comparative Study of Neuroprotective Activity of Mucuna pruriens and Withania somnifera Against Haloperidol Induced Parkinson’s Disease in animal model (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Parkinson’s Disease (PD), initially was a challenging Neurodegenerative Disorder (ND) to treat and manage, but translational research bridged the gap to its risk factors, pathophysiology, diagnosis, treatment and management. Research is more focused on neuroprotection with the purpose of preventing neuronal loss reaching more than 60% exhibiting symptomatic PD, and neuro-rescue to restore functionality to partly damaged cells. Thus, this comparative study investigated Mucuna pruriens and Withania somnifera’s neuroprotective properties, as this may help to uncover and establish similar pathways in their mechanisms of action, and/or differences to determine if synergism may be possible. The administration of haloperidol resulted in significant motor damage, oxidative stress, and also high pro-inflammatory cytokines. M. pruriens and W. somnifera extract pre-treatment showed dose-dependent beneficial effects on behavior parameters, enhancing GSH levels and decreasing LPO levels, and remarkably reduced the levels of inflammatory cytokines. These results were corroborated by histopathological analysis of brain tissues, which indicated well-preserved brain neuronal integrity and limited evidence of neurodegeneration. Moreover, the in vitro MTT test using Neuro-2a cells showed that both extracts were able to support high cell viability; it is implied that the extracts may possess cytoprotective potentials on the cellular level. The experiment shows that Mucuna pruriens and Withania somnifera have substantial neuroprotective and anti-inflammatory effects on haloperidol-induced neurotoxicity, W. somnifera having a better overall outcome as compared to M. pruriens.